2004
DOI: 10.1097/00042737-200404000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis

Abstract: Our data suggest an important role of vascular endothelial growth factor in counteracting the local imbalance of fibrogenesis and fibrolysis, leading to an accumulation of immature subepithelial matrix in collagenous colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…VEGF limits the release of TIMP-1 by endothelial cells, thereby increasing MMP-1 activity (16, 45). In the epithelium and in inflammatory cells of the lamina propria, expression of VEGF reflects an important physiological mechanism counteracting the MMP-1/TIMP-1 imbalance in CC; disinhibiting MMP-1 and reducing levels of TIMP-1 leads to an accumulation of immature subepithelial ECM in CC (87). An increased immunostaining for VEGF within the epithelium is also maintained when clinical and histological remission is achieved, suggesting the persistence of the repair mechanism (87).…”
Section: Histological Markersmentioning
confidence: 99%
“…VEGF limits the release of TIMP-1 by endothelial cells, thereby increasing MMP-1 activity (16, 45). In the epithelium and in inflammatory cells of the lamina propria, expression of VEGF reflects an important physiological mechanism counteracting the MMP-1/TIMP-1 imbalance in CC; disinhibiting MMP-1 and reducing levels of TIMP-1 leads to an accumulation of immature subepithelial ECM in CC (87). An increased immunostaining for VEGF within the epithelium is also maintained when clinical and histological remission is achieved, suggesting the persistence of the repair mechanism (87).…”
Section: Histological Markersmentioning
confidence: 99%
“…The detection of the same cells by the antibody raised specifically against VEGF 165 b, as by an antibody to all VEGF isoforms, concurs with our ELISA findings that in normal colonic mucosa it is the VEGF xxx b isoforms that predominate. This has significant implications for interpretation of all previous studies investigating VEGF expression in the colon, not only for tumour studies (Hurwitz et al , 2004), but also for collagenous (Griga et al , 2004) and ischaemic colitides (Okuda et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that VEGF promotes angiogenesis during acute inflammation and ischemia (42,43). VEGF also plays a role in counteracting the local imbalance of fibrogenesis and fibrolysis, leading to an accumulation of immature subepithelial matrix in collagenous colitis (44). Using intravital microscopy of the rat mesenteric microcirculation to measure leukocyte-endothelium interactions, Scalia et al (45) demonstrated that VEGF inhibits leukocyte-epithelial cell adherence and the effects of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%